Samir Amin : Intellectuel organique au service de l'emancipation du sud - Dembele, Demba Moussa (Book collections on Project MUSE., 2011)
This book on Professor Samir Amin retraces his family origins, intellectual itinerary, political struggles as well as his experience in economic policy formulation in Egypt, Mali and many other countries. The fundamentals which shaped Samir Amin's thinking, directed his life-long work and influenced his action spawned from his early discovery in high school of Marxism and Historical Materialism, used as a scientific analysis of the history of human societies. This book also highlights Samir Amin's invaluable contribution to the struggle against capitalism through his indefatigable fight to deconstruct the concepts that are used to disguise the true face of historical capitalism, which is nothing but an unabashed pursuit for accumulation and dispossession of dominated countries and peoples. Through a series of interviews with Samir Amin, the author unravels the poignant and great ideas which have been at the heart of his intellectual and political fight for the last half century. The author also provides a selection of texts which includes an exhaustive bibliography, with all published writings of Samir Amin in French. This rich work is meant for a large readership--students, researchers, teachers, political leaders and citizens who are interested in the phenomenon of globalisation and its impact on the so-called 'under-developed countries.